Thermal comfort analysis at Universiti Putra Malaysia Health Centre - Aminuddin, Alina (2013)
Thermal comfort analysis in any waiting areas is crucial to assess the conditions that will influence the occupants state of well being. The hot and humid environments of Malaysia can easily affect the waiting room conditions if steps are not taken to create a comfortable atmosphere. The occupants can feel aggravated and stressful while waiting for their turn to see the medical officer if the conditions at the waiting rooms are not comfortable. The main objective of this research was to determine the thermal comfort of occupants in various waiting areas at Universiti Putra Malaysia (UPM) Health Centre seeking medical attention and to evaluate the possibility of using the Infrared Thermography for fast screening of body temperature from a distance. At the same time, a survey was performed involving the said occupants on their perception of thermal comfort. Thermal comfort field measurements study was conducted in the Health Centre of UPM. Relative humidity, mean radiant temperature, air temperature, air velocity, clothing insulation, metabolic rate, Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) were calculated. The subjective survey involved questions on thermal sensation. The result yielded from subjective and objective approach was used to formulate the conclusion on thermal comfort at the Health Centre. For thermal comfort evaluation, a questionnaire according to ASHRAE Standard 55 was given to all occupants who participated in the temperature screening by the Infrared Thermography. Fanger’s Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) were calculated using measurement obtained from Heat Stress Monitor. At any given condition of a waiting room, thermal comfort may also influence body temperature of occupants. The Infrared Thermography is a potential solution to diagnose the human body temperature from a distance. The ability of this technique to differentiate different body temperatures is of practical importance in cases which require rapid screening to segregate infected occupants during mass pandemic such as HIN1 infection that occur at UPM in 2009. The study involved screening of 313 occupants at the Health Centre. Each occupant’s body temperature was determined by recording the temperature profile of the face using the Infrared Thermography device Fluke Thermal Imager. The subject was seated at a distance of about 1.0 meter away from the device. The temperature profile was analyzed using the SmatView 2.0 to determine the body temperature. The air temperature at the Health Centre measured by the Thermal Stress Monitor was between 19°C to 21°C, lower than the value given by the ANSI/ASHRAE Standard (2004) and ISO 7730 (2005) of 24°C set to be the lower limit for thermal comfort. It was observed that 63% of occupants involved in the study were comfortable with the surrounding air temperature. PMV showed the most acceptable value was at -1.1 and PPD showed the most acceptable value at 30.5. The results showed that a difference of about 1.1% and 5.1% was observed between the Infrared Thermography reading and the values obtained by using the Digital Clinical Thermometer and laboratory thermometer, respectively. The results were verified by a senior medical officer at the UPM Health Centre. Out of 313 occupants tested by Infrared Thermography, 38.9 % showed body temperature of 37-38ºC, 34.8% showed 38-39ºC, 14.1% showed 36-37ºC, 8.3% showed 39-40ºC and lastly, 3.5% showed 35-36ºC. The Infrared Thermography device could be used effectively for fast screening body temperature without any personal contact with the patient, as the recordings could be done 1-2 meters away. This method could reduce 50% of screening time compared to the normal clinical method. The results from PMV and PPD study comply with the findings on the thermal sensation of occupants in the waiting area. The study also shown that not only Infrared Thermography was applicable to measure the surface body temperature of material, but it also can be used to measure the human body temperature.